2022
DOI: 10.46542/pe.2022.221.2332
|View full text |Cite
|
Sign up to set email alerts
|

Virtual OSCE: Experience and challenges with a large cohort of pharmacy students

Abstract: In response to the inability to conduct conventional face-to-face objective structured clinical examination (OSCE) due to the COVID-19 lockdown, this study explored options to design virtual OSCE (vOSCE) that meets the objectives and standards of effective competency-based assessment for a large cohort of pharmacy students. The vOSCE required advanced planning of the actual assessment and technical conduct. The development of a master plan consisting of the types of competencies to test, topics and number of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 17 publications
(17 reference statements)
1
8
0
Order By: Relevance
“…Additionally, our study found that OC-OSCE appropriately assessed communication skills, professionalism, and attitudes compared to the V-OSCE. This finding is in parallel with the findings of other studies (Branch, 2014, Zulkifly et al, 2022 , Ganesananthan et al, 2021 ). In all these studies, students preferred the OC-OSCE as a better communication tool with the patient as well as the examiner.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Additionally, our study found that OC-OSCE appropriately assessed communication skills, professionalism, and attitudes compared to the V-OSCE. This finding is in parallel with the findings of other studies (Branch, 2014, Zulkifly et al, 2022 , Ganesananthan et al, 2021 ). In all these studies, students preferred the OC-OSCE as a better communication tool with the patient as well as the examiner.…”
Section: Discussionsupporting
confidence: 92%
“…Online teaching was a kind of shift that many pharmacy and medical schools targeted worldwide, especially after the COVID-19 pandemic ( Mak et al, 2022 , Prettyman et al, 2018 , Lim et al, 2020 ). V-OSCE has been discussed by several studies concerning medical and pharmacy students and was found to be a reasonable solution that relatively retains the same ability to assess various clinical skills and clinical reasoning, history-taking, and formulating management plans and differential diagnoses as compared to the conventional OC-OSCE ( Grover et al, 2022 , Lim et al, 2020 , Zulkifly et al, 2022 ). Moreover, few studies discussed the advantages of V-OSCE over the on-campus format that include but are not limited to: reduction in travelling time, undertaking the exam in a comfortable environment, and the potential of scaling-up with smoother logistics ( Grover et al, 2022 , Dost et al, 2020 , Blythe et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this time-constrained context of clinical-skill training and assessment, the development of innovative digital strategies to pursue high-quality medical education while ensuring social distancing has been a key goal of many medical and other health schools[ 6 ]. Although several online OSCE (eOSCEs) experiences have been reported to be using a computer-based program [ 7 ] or generic teleconference systems [ 8 , 9 ], Zoom teleconferencing has been more widely used during the pandemic either for lectures[ 10 ], tutoring sessions, or for eOSCEs [ 4 , 11 , 12 ]. Many schools acquired a Zoom license, and both students and teachers were familiar with its use.…”
Section: Introductionmentioning
confidence: 99%